2022
DOI: 10.4049/jimmunol.2100799
|View full text |Cite
|
Sign up to set email alerts
|

Effective Barriers: The Role of NKT Cells and Innate Lymphoid Cells in the Gut

Abstract: The critical role of commensal microbiota in regulating the host immune response has been established. In addition, it is known that host–microbial interactions are bidirectional, and this interplay is tightly regulated to prevent chronic inflammatory disease. Although many studies have focused on the role of classic T cell subsets, unconventional lymphocytes such as NKT cells and innate lymphoid cells also contribute to the regulation of homeostasis at mucosal surfaces and influence the composition of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 216 publications
(217 reference statements)
0
6
0
Order By: Relevance
“…2d and 2e) showed a reduction in almost all LP CD4 + T cell populations in KD-fed mice. Only LP natural killer T cells and type 3 innate lymphoid cells (GF LP) were increased – both have been associated to gut homeostasis and health 10 . Finally, the expression of both subunits of calprotectin (a biomarker of inflammation used in inflammatory bowel disease 11 ) was reduced in the spleens of GF KD-fed mice (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2d and 2e) showed a reduction in almost all LP CD4 + T cell populations in KD-fed mice. Only LP natural killer T cells and type 3 innate lymphoid cells (GF LP) were increased – both have been associated to gut homeostasis and health 10 . Finally, the expression of both subunits of calprotectin (a biomarker of inflammation used in inflammatory bowel disease 11 ) was reduced in the spleens of GF KD-fed mice (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The functional activity of NKT cells is realized through effector (perforin/granzyme and/or FasLmediated) mechanisms and regulatory (cytokine production) providing the relationship between innate and adaptive immunity [6,12,40]. The subset composition of NKT cells is determined by CD16 and CD56 receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the functional activity of NKT cells is realized in various mechanisms of the immune response, realizing the relationship between natural resistance and adaptive immunity. This lymphocyte subset is involved in the mechanisms of antiviral and antiparasitic protection, and also secreted different immunoregulatory cytokines in the site of inflammation [1,10,12]. In addition, NKT cells are able to stimulate and inhibit antitumor immune responses [9,39].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we did not observe significant overlap of these two pathways in the 8 mononuclear phagocytic populations (Figure 6C). However, when we performed RNA velocity analysis that imputes cell fates (53,54,61,(84)(85)(86)(87)(88), we identified a robust directional flow from the efferocytosis high C1QC + macrophages towards the inflammasome rich NLRP3 + subset through an intermediate ISG15 + macrophage state (Figure 6E, Supplementary Figure S4, Supplementary Tables S6). We observed that another efferocytosis-rich cluster, SPP1 + , can also develop into the NLRP3 + macrophage subset (Figure 6E).…”
Section: Efferocytosis Induces Il1b Signature In Macrophagesmentioning
confidence: 99%